Implementing Authentic Assessment for Assessing Higher Order Thinking Skill (HOTS) in Curriculum 2013 - Thea Karuni Respati (UPT Publikasi dan Penerbitan Universitas San Pedro, 2023)
This review of the literature investigates the implementation of authentic assessment methods to effectively assess Higher Order Thinking Skills (HOTS) in the context of Curriculum 2013 (K-13). As emphasis on fostering students' critical thinking, problem-solving, and creativity increases, the need for reliable and valid assessment techniques has become of the highest level. The research investigates an extensive number of scientific articles, research papers, and educational resources published between 2013 and 2023. This paper examines, through a systematic review, authentic assessment strategies that have been used to evaluate HOTS in the K–13 education system. The review demonstrates the potential advantages of authentic assessment for enhancing students' cognitive abilities, motivation, and knowledge application in real-world settings. In addition, it discusses the difficulties and effects of integrating authentic assessment into the curriculum. This literature review seeks to assist educators, policymakers, and curriculum developers in designing effective assessment practices that correspond with the transforming educational context while supporting the development of learners' critical thinking skills.